2020
DOI: 10.1002/ddr.21760
|View full text |Cite
|
Sign up to set email alerts
|

Role of mineralocorticoid receptor antagonists in kidney diseases

Abstract: Mineralocorticoid receptor (MR) antagonists, for example, spironolactone and eplerenone, are in clinical use to treat hypertension. Increasing evidence suggests that mineralocorticoid receptor activation causes the pathogenesis and progression of chronic kidney disease. Aldosterone‐induced MR activation increases inflammation, fibrosis, and oxidative stress in the kidney. MR antagonists (MRAs) have demonstrated therapeutic actions in chronic kidney disease (CKD), diabetic nephropathy (DN), renal fibrosis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 172 publications
2
40
0
2
Order By: Relevance
“…This may be associated with the treatment mechanism of MRAs. MRA use increases sodium excretion and decreases potassium excretion in the kidney, resulting in an increase in serum potassium levels (35). Even though the incidence of hyperkalaemia was increased in comparison with that in the placebo group, finerenone is associated with a lower risk than classic steroidal MRAs (spironolactone or eplerenone) according to recent trials and meta-analyses (30,35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be associated with the treatment mechanism of MRAs. MRA use increases sodium excretion and decreases potassium excretion in the kidney, resulting in an increase in serum potassium levels (35). Even though the incidence of hyperkalaemia was increased in comparison with that in the placebo group, finerenone is associated with a lower risk than classic steroidal MRAs (spironolactone or eplerenone) according to recent trials and meta-analyses (30,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…MRA use increases sodium excretion and decreases potassium excretion in the kidney, resulting in an increase in serum potassium levels (35). Even though the incidence of hyperkalaemia was increased in comparison with that in the placebo group, finerenone is associated with a lower risk than classic steroidal MRAs (spironolactone or eplerenone) according to recent trials and meta-analyses (30,35,36). Current research has reported that compared with eplerenone, finerenone has a much better effect on preventing cardiac fibrosis and improving strain parameters in mice (37).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that overactivation of the mineralocorticoid receptor (MR) results in renal fibrosis and is closely linked to the progression of renal injury in DKD ( Shrestha et al, 2019 ; Patel et al, 2020 ). Therefore, new drugs targeting MR are considered as potential therapies that slow the progression of renal fibrosis.…”
Section: New Therapies For Renal Fibrosismentioning
confidence: 99%
“…Mineralocorticoid receptor antagonists (MRAs) have demonstrated beneficial effects on renal inflammation in various animal studies, directly regulating inflammatory cell function and indirectly suppressing proinflammatory cytokines, chemoattractants, and pro-oxidants, increasing anti-inflammatory cytokines in kidneys [ 88 ]. Spironolactone and eplerenone in particular demonstrated beneficial effects, reducing the kidney’s inflammatory markers [ 89 , 90 ].…”
Section: Introductionmentioning
confidence: 99%